Doxycycline—a role in ocular surface repair. Issue 5 (16th April 2004) - Smith, V A; Cook, S D
Abstract : Background/aims: Doxycycline is a broad spectrum antibiotic that chelates metal ions and is frequently used as part of the treatment of ocular surface diseases. Its therapeutic value has been ascribed to an ability to inhibit matrix metalloproteinase (MMP) activity and both MMP and IL-1 synthesis. The aim of this study was to evaluate the role of doxycycline as an inhibitor of corneal MMPs and assess its contribution to ocular surface repair mechanisms. Methods: Corneal epithelial cell and keratocyte cultures were grown to confluence and incubated with IL-1α, LPS, doxycycline, or doxycycline and LPS in serum free medium for 4 days. The cells were either harvested and assayed for caspase-3 activity or stained with either AE5 or antivimentin antibodies. Media samples were concentrated and assayed for MMP activity by zymography or using a fluorigenic substrate. ELISA was used to quantify IL-1α, MMPs -1, -2, -3, -9, and TIMPs -1 and -2. Results: IL-1α and LPS had no effect on MMP/TIMP production by cultured corneal epithelial cells and keratocytes. Corneal MMP-2 inhibition by doxycycline was partially [Ca 2+ ] dependent but irreversible. At the minimum inhibitory concentration, 100 μm, doxycycline had no apparent effect on MMP and TIMP production, but ultimately caused the death of keratocytes and some of the epithelial cells that detached from their basement membrane. Caspase-3 activity was not detected in dead or dying keratocytes. The mechanism of cell death in cultured corneal epithelial cells was not caspase-3 related apoptosis as the activity of this enzyme, normally detectable, was lost. The epithelial cells that survived doxycycline treatment did not bind antivimentin antibody and compared with controls, reacted less with the AE5 antibody. They were probably transient amplifying cells. Conclusions: Doxycycline irreversibly inhibits corneal MMP-2 activity by chelating the metal ions that are catalytically and structurally essential. Corneal MMP/TIMP production in vitro is not modulated by IL-1α, LPS, or doxycycline. The therapeutic value of doxycycline may depend upon its effective concentration at the ocular surface and probably relates to its chelating properties.